Kościuszko mound in Cracow – a monument of history. Maintenance, management, promotion: Treść ideowa zabytku. Odrobina historii. - Rokosz, Mieczysław (Protection of Cultural Heritage, 2019)
Kościuszko Mound, built in 1820-1823 by the Polish Nation as a symbolic grave and monument to Tadeusz Kościuszko, is the second significant sub-dominant feature in the cultural landscape of Cracow, next to Wawel Castle. In the mid-19th century, a citadel fort with neo-style features was built around the Mound, considered a masterpiece of architecturae militaris. In 1936, the Mound was entered into the register of monuments and in 2017, by decree of the President of the Republic of Poland, together with its surroundings, it was declared a Monument of History. As an earthen structure, the Mound is subject to constant processes of destruction caused by the forces of nature. The Committee of the Kosciuszko Mound established in 1820 is responsible for its permanent conservation. The Committee also takes care of the surroundings of the Monument by restoring components of the fort. The great success of the conservation and adaptation works is the transformation of the southern curtain (i.e. the earth rampart fortified with a wall, with a ramp for rolling out cannons) into a multi-cubature, two-storey conference and exhibition centre. The Committee also led to thinning the canopy of the self-seeding forest around the Mound and in the foreground of the fort, in order to expose this historic complex. In other parts of the fort, subordinate to the Committee, Kościuszko exhibitions are held, and ultimately the Kościuszko Museum is to be established here. Among the projects aimed at promoting the Kosciuszko Mound with its surroundings as an object of historical, architectural and landscape values - material and immaterial – there are numerous publications in Polish and foreign languages, lectures given in Poland, but also in the United States, France, Switzerland and Australia. The best evidence of the well-established place of Kosciuszko Mound in the Polish space and geography of the Globe and in the consciousness of Poles and many foreigners is the huge and steadily growing visitor turnout.